The changing landscape of plant sciences : (Acc: 2299) taxonomy & ecology : a festschrift for Prof. S.D. Sabnis - Sabnis, S. D.; Daniel, M., Dr. (Dehra Dun : International Book Distributors, 1997)
Contributed articles; brought out in honor of the former Pro-Vice-chancellor of M.S. University, Baroda.
Keywords: Toxonomy & Ecology; Plant ecology